Pretreatment serum level of interleukin-6 predicts carfilzomib-induced hypertension in relapsed/refractory multiple myeloma. Issue 7 (7th June 2022) - Muramatsu, Ayako; Kobayashi, Tsutomu; Kawaji-Kanayama, Yuka; Uchiyama, Hitoji; Sasaki, Nana; Uoshima, Nobuhiko; Nakao, Mitsushige; Takahashi, Ryoichi; Shimura, Kazuho; Kaneko, Hiroto; Kiyota, Miki; Wada, Katsuya; et al.
Abstract: Carfilzomib (CFZ) constitutes powerful combinatory therapy for relapsed/refractory multiple myeloma (RRMM); however, cardiovascular adverse events (CVAEs) have been shown as major treatment obstacles with the use of CFZ. Along with our multi-institutional prospective observational study by the Kyoto Clinical Hematology Study Group on the efficacy and safety of CFZ-based treatments (UMIN000025108), we here performed an ad hoc analysis of CFZ-related CVAEs in 50 patients with RRMM. We analyzed the association between CFZ-related CVAEs and pre-planned examinations, including patients' background, electrocardiographic findings, echocardiographic findings, and serum/plasma levels of 18 potential candidate biomarkers. The common CVAEs were hypertension (42%), arrhythmia (14%), and prolongation of QT corrected interval (10%), whereas no serious CVAEs occurred. The pretreatment serum level of interleukin-6 was identified as a significant risk factor for CFZ-related hypertension. This study revealed hypertension as the most frequent CFZ-related CVAE and suggested that baseline serum interleukin-6 is a useful predictor for CFZ-induced hypertension.